MODEL FOR THE RELIABILITY, AVAILABILITY AND SAFETY OF THE CONTROL CENTERS OF THE VESSEL TRAFFIC MANAGEMENT AND INFORMATION SYSTEMS - Ristov, Pančo (Promet - Traffic&Transportation, 2013)
The quality of Vessel Traffic Management and Information Systems depends on the quality of all subsystems, in particular the quality of control centers. The most commonly used quantitative indicators of the control centers’ quality are: reliability, availability, safety, and system failure. Therefore, a block diagram of reliability and the model for reliability / availability (Markov model) have been created in this paper and a detailed analysis and calculation of the quantitative indicators of critical components (servers) of the control center have been performed. The quality functioning of the control centers will enable gathering, processing, storing and dissemination of timely, safe, and reliable data and information to the services in charge of monitoring and management of maritime traffic.